Los exiliados económicos. La nueva emigración española a Argentina (2008-2015) - Rodríguez-Fariñas, J.; Romero-Valiente, J.-M.; Hidalgo-Capitán, A.-L. (Revista Iberoamericana de Estudios de Desarrollo)
The article analyzes the Spanish emigration to Argentina between 2008 and 2015, with the prospect of understanding the demographic profile of the new Spanish emigrants to Argentina, the causes of their migration, the initial problems of migration process, the conditions of their later situation and their expectations of the future. We use a mixed quantitative and qualitative methodological strategy, combining first and second order research. Findings include that these migrants are mostly young and middle-aged workers, highly qualified and with work experience. Pushed from Spain by the economic crisis and attracted to Argentina for its labor opportunities, they have found a migratory and institutional network of support which guarantees a social, labor and economic integration. For the most part, they are satisfied with their migratory experience even though most desire to come back to Spain.